Evaluación de la medulación de fibras de lanas y fibras especiales de algunas especies de animales - Berolatti Obando, Giancarlo (2021)
There are arguments in favour of reducing the incidence of medullation to improve fibres quality from the point of view of textile production and processing, and therefore it is necessary to reinforce the knowledge of this characteristic. Based on that, this study aimed to evaluate the incidence and relationship between the types of medullation, as well as to determine its relationship with the fineness in fibres of sheep, alpaca, llama, paco-vicuña and Angora rabbit. Samples of wool and fibre (n=15 per animal species) and additionally 140 samples of white male tuis alpacas were collected. The mean fibre diameter (MFD) and the percentages of medullated (% MF) and non-medullated (% NMF) fibres were determined, and in the latter, the percentages of fibres with fragmented, discontinuous, continuous and strongly medullated or kemp-type medullation were determined. Results showed that Merino wool fibres presented few medullary fibres, the opposite occurred in Angora rabbit fibres, while the fibres of alpaca tuis, llamas and paco-vicuñas had moderate percentages of medullation (22-40%), with medullary still found in very high fine fibres. A direct relationship between MFD and %MF was determined in all types of fibres, except for sheep wool. It is concluded that the %MF is a characteristic that should be diminished in llamas and alpacas and, therefore, it should be considered as a selection criterion in genetic improvement programmes, but only to reduce the incidence of strongly medullated fibres.